Determinants Of The Timeliness Of Financial Reporting of Go Public Companies In The Covid-19 Pandemic: Evidence From Indonesia - Purwanti, Noer Indach; Rochmatullah, Mahameru Rosy; Witono, Banu; Putri, Eskasari (Akuisisi: Jurnal Akuntansi, 2023)
Purpose: This paper aims to analyze whether profitability, auditor opinion, institutional ownership, and the Covid-19 pandemic have an impact on the timeliness of financial reporting. The researcher explores several online and conventional publication documents related to the operations of publicly listed companies in Indonesia.Method: Employing binary logistic regression, this study analyzes the 175 sampled firms. Some of the testing components include profitability, audit opinion, institutional ownership, and the Covid-19 pandemic.Findings: The results of the analysis show that the company's profitability and activity restrictions due to the Covid-19 pandemic have a substantial impact on the timeliness of reporting. In theory, this study provides an understanding that financial performance determines the compliance of managers in informing financial reporting to stakeholders. In practice, extraordinary events on an international scale such as the Covid-19 pandemic have thwarted financial reporting accountability. The COVID-19 pandemic has an impact on the timeliness of financial reporting, which includes parties directly related to the issuance of audited financial statements including reporting entities and auditors/public accountants, parties indirectly related to financial reporting including accounting professional associations, and the tools used by these parties in financial reporting including Financial Accounting Standards, auditing standards and laws and regulations, professional codes of ethics, and professional certifications. The impact is on the significance of assessments and estimates, going concern, internal control, audit committee governance, events after the reporting period, accessibility of audit evidence and guidance for parties related to financial reporting.